Citation indexes as an instrument for evaluating the results of scientific research and forming the list of scientific information resources - N. Yu. Beryozkina; O. N. Sikorskaya; G. S. Khrenova (Библиосфера)
The results of scientific research conducted by the Central Scientific Library of the National Academy of Sciences of Belarus based on the use of the «Web of Science» and «Scopus» databases, the degree of reflection of the Belarus authors’ articles, as well as the publications supported by various foundations, citation data, etc., and their use for evaluating scientific activity and the quality of scientific information resources access to which is provide by the Central Science Library of the National Academy of Sciences.